2021
DOI: 10.3389/fcvm.2021.710053
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methylation Related Therapeutic Challenge in Cardiovascular Diseases

Abstract: The epidemic of cardiovascular diseases (CVDs) is predicted to spread rapidly in advanced countries accompanied by the high prevalence of risk factors. In terms of pathogenesis, the pathophysiology of CVDs is featured by multiple disorders, including vascular inflammation accompanied by simultaneously perturbed pathways, such as cell death and acute/chronic inflammatory reactions. Epigenetic alteration is involved in the regulation of genome stabilization and cellular homeostasis. The association between CVD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 171 publications
(221 reference statements)
0
20
0
Order By: Relevance
“…Inhibition of NF-κB has important clinical significance in the treatment of asthma. 27,29 In addition, multiple drugs treat or improve asthma through this signaling pathway. For example, Korean Red ginseng affected the ovalbumin (OVA)-induced asthma by modulating the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of NF-κB has important clinical significance in the treatment of asthma. 27,29 In addition, multiple drugs treat or improve asthma through this signaling pathway. For example, Korean Red ginseng affected the ovalbumin (OVA)-induced asthma by modulating the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation on the lysine residues can be mono-(me), di-(me2), or tri-(me3) on the ε-amino group, whereas for arginine, it can be mono-(me) or di-(me2s) symmetrically or asymmetrically (me2a) ( Kim et al, 2019 ). Histone methylation can be added by histone methyltransferase (HMTs), catalyzing the transfer of a methyl group from S-adenosylmethionine to their targeted residues ( Yang et al, 2021 ). Typically, HMTs are composed of three families: the SET-domain containing enzymes, Dot1-like proteins, and arginine N-methyltransferase enzymes (PRMTs, Figure 1 ; Table 1 ) ( Michalak and Visvader, 2016 ).…”
Section: Histone Methylationmentioning
confidence: 99%
“…Studies suggested that epigenetic regulation exerts a pivotal role in many diseases such as cancers and CVDs ( Liu et al, 2021 ; Yang et al, 2021 ). Distinct from genetic alteration, epigenetic modification is reversible, and the inhibitor of epigenetic alteration provides a novel insight into searching pharmaceutical therapeutic targets ( Pons et al, 2009 ).…”
Section: Epigenetic Regulation Of Atherosclerosismentioning
confidence: 99%